Case Report: Transcatheter treatment of aortic coarctation in a 58-year-old patient with LACHT syndrome and left lung agenesis - Tu, Qingxian; Huang, Nanqu; Guo, Fujia; Luo, Minhong; Xu, Min; Liu, Jiaji; Yuan, Zhengqiang; Jiang, Qianfeng (Frontiers in Cardiovascular Medicine, 2023)
LACHT (Lung Agenesis, Congenital Heart, and Thumb anomalies) syndrome is an extremely rare congenital anomaly and presents significant challenges in adults due to its poor survival rates. Herein, we report a case of late diagnosis and successful transcatheter treatment of aortic coarctation in a 58-year-old male patient with LACHT syndrome, medically resistant arterial hypertension, and left lung agenesis. Baseline CT angiography showed isthmic aortic coarctation and left lung agenesis, with compensatory right pulmonary artery and vein thickenings. The patient underwent balloon dilation and subsequent implantation of a covered NuMED 45 mm 8-ZIG CP stent with satisfactory outcomes. The pressure gradient decreased from 43 to 23 mmHg. The arterial pressures normalized during the follow-up with fewer medications. Genetic testing identified a heterozygous mutation (c.6583C > T) in the FBN2, supporting the diagnosis of variant Marfan syndrome.